Establishing the female voice in contemporary Nigerian narrative through nego-feninism: a study of Abubakar Gimba’s sacred apples - Muhammad, Nasiru Umar; Talif, Rosli; Kaur, Hardev; Bahar, Ida Baizura (Universiti Putra Malaysia Press, 2016)
In this study we carry out a comparative analysis between titles of research papers published in the most authoritative specialized European and US-based astrophysics journals written in English and titles of articles on astrophysics published in Scientific American Magazine, the most prestigious English-written journal in the divulgation of science. We specifically address issues related to three linguistic variables: title length, title lexical density and title type. Our main results show that titles of research papers published in scientific journals are much longer than titles of articles published in Scientific American Magazine. Lexical density is also higher in scientific titles than in popular science ones. Scientific American Magazine titles are formulated in a clear and direct way, with no syntactic complexity. They consist primarily in simple and nominal constructions with a low presence of adjectives, compound groups and technical terminology. The predominance of nominal compounds over adjectival ones and the use of proper names, which mainly refer to well-known stars, planets, satellites and galaxies, imply that popular science titles usually deal with more global and well established concepts. The higher number of verbal titles and of definite articles in popular science titles when compared to scientific titles may also be interpreted as a greater desire to generalize the ideas presented. This study may be applied to languages other than English and would surely be of the utmost importance to determine the design of titles of scientific and popular science papers, not only in astrophysics but also in other fields.